A geopolymer-based bifunctional structure supercapacitor and a preparation method thereof
Patent Information
- Application Number
- CN202611406147.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]然而,现有研究多聚焦于地聚合物的结构或孔结构单一性能,对于如何通过碱性激发剂配方调控其多尺度孔结构,进而协同提升抗压强度与双电层电容性能,缺乏系统性的工艺参数指导
[0016]与现有技术相比,本发明的优点包括:
Smart Images

Figure CN122889598A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energy storage dual-functional materials technology, and particularly relates to a geopolymer-based dual-functional supercapacitor and its preparation method. Background Technology
[0002] Currently, multifunctional structural materials that combine load-bearing and energy storage functions are gaining increasing attention. Traditional civil engineering materials only provide mechanical support, while conventional supercapacitor energy storage devices exist as independent components, making it difficult to achieve organic integration of structure and function, and thus failing to meet the "structure-function integration" requirements of smart infrastructure. Structural supercapacitors integrate high specific surface area electrode materials, electrolytes, and a mechanically robust matrix, enabling the component to store electrical energy while bearing external loads.
[0003] In structural supercapacitor systems, the membrane material must balance high porosity, good electrolyte permeability, sufficient mechanical strength, and thermal stability. Existing technologies, such as olefin porous membranes, cellulose membranes, epoxy resins, and cement-based materials, have all been attempted to construct such systems, but they generally share the common technical bottleneck of difficulty in coordinating mechanical and electrochemical properties. Geopolymers, as low-carbon emission aluminosilicate inorganic polymers, possess a three-dimensional gel network rich in multi-scale pores, theoretically capable of simultaneously meeting the requirements for ion transport and mechanical support.
[0004] However, existing research largely focuses on the single properties of geopolymer structures or pore structures. There is a lack of systematic process parameter guidance on how to regulate multi-scale pore structures through alkaline activator formulations to synergistically improve compressive strength and double-layer capacitance. In particular, the mechanism by which the modulus of the alkaline activator affects the interfacial compatibility, pore size distribution, and ion migration pathways of geopolymer membranes remains unclear, hindering the practical application of geopolymer-based supercapacitors. Summary of the Invention
[0005] The main objective of this invention is to provide a geopolymer-based bifunctional supercapacitor and its preparation method, so as to overcome the shortcomings of the prior art.
[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes: According to a first aspect of the present invention, a method for preparing a geopolymer-based bifunctional supercapacitor is provided, comprising the following steps: S1. Prepare an alkaline activator solution, wherein the modulus of the alkaline activator solution is 0.6 to 1.4, and the alkaline equivalent based on sodium oxide is 11%; S2. Mix metakaolin and the alkaline activator solution at a liquid-to-solid ratio of 0.5 to obtain geopolymer slurry; cast the geopolymer slurry into a mold and cure it to obtain a geopolymer structured electrolyte membrane. S3. Inject an electrolyte solution into the geopolymer structure electrolyte membrane; S4. Two activated carbon electrodes are respectively attached to the opposite sides of the geopolymer structure electrolyte membrane to obtain a dual-function supercapacitor.
[0007] Furthermore, the mixing is carried out in a planetary mortar mixer at low speed for 120 seconds and high speed for 120 seconds in sequence.
[0008] Furthermore, the curing process involves: demolding after standing at room temperature for 24 hours, and then curing at room temperature for 28 days.
[0009] Furthermore, the electrolyte solution is a 0.5 mol / L sodium sulfate aqueous solution.
[0010] According to a second aspect of the present invention, a geopolymer-based bifunctional supercapacitor prepared by any one of the methods described herein is provided, comprising a geopolymer-structured electrolyte membrane, an electrolyte solution, and two symmetrically arranged activated carbon electrodes; The geopolymer structured electrolyte membrane is formed by polymerizing metakaolin clay with an alkaline activator having a modulus of 0.6 to 1.4. The geopolymer structured electrolyte membrane has an intrusive porosity of 40% to 44% and a most probable pore size of 119 nm to 430 nm.
[0011] Furthermore, the alkaline activator is a composite alkaline activator of sodium hydroxide and sodium silicate.
[0012] Furthermore, the activated carbon electrode comprises activated carbon, conductive carbon black, and polytetrafluoroethylene binder, wherein the mass ratio of activated carbon, conductive carbon black, and polytetrafluoroethylene binder is 85:10:5.
[0013] Furthermore, the active material loading of the activated carbon electrode is 5 mg / cm³. 2 The activated carbon is Kuraray capacitor carbon YP-50F, and the conductive carbon black is Super P Li.
[0014] Furthermore, in the geopolymer structure electrolyte membrane, the volume percentage of pore segments with a pore size greater than 200 nm is 1.5% to 39.4%.
[0015] Furthermore, the 28-day compressive strength of the geopolymer structure electrolyte membrane is 11.5 MPa to 15.3 MPa.
[0016] Compared with the prior art, the advantages of the present invention include: This invention achieves directional control of the multi-scale pore structure of the metakaolin geopolymer gel network by controlling the modulus of the alkaline activator between 0.6 and 1.4 and fixing the alkali equivalent and liquid-solid ratio. This invention reveals that increasing the modulus promotes a shift in the internal pore structure of the geopolymer from coarse, interconnected pores (>200nm, accounting for as much as 39.4%) to fine pores (119nm–430nm most probable pore size). This optimized pore size distribution significantly weakens the interconnected coarse capillary network, resulting in a substantial increase in the 28-day compressive strength from approximately 4.8 MPa at low modulus to 15.3 MPa at high modulus, effectively addressing the low mechanical properties of traditional geopolymer membranes. Furthermore, this invention, while ensuring mechanical strength, avoids the problem of hindered ion migration caused by excessive pore density at high modulus levels by precisely controlling the pore size distribution. Experiments have shown that the product of this invention with a modulus of 1.0 to 1.2 can maintain high electrolyte wettability and ion transport rate while achieving a compressive strength of 11.5 MPa to 15.3 MPa, and its specific capacitance can reach 232.51 F·g. -1 (1.0 module), and the assembled supercapacitor, after being charged to 3V in three series, can successfully power a green LED bulb for up to 3 minutes, verifying its potential for practical energy storage applications. Furthermore, the manufacturing process of this invention is simple and environmentally friendly, using low-cost metakaolin and industrial water glass as raw materials. Stable products can be obtained through room temperature curing, making it suitable for large-scale production and providing a feasible solution for distributed energy storage components in smart infrastructure. Attached Figure Description
[0017] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings: Figure 1 A process flow diagram for fabricating the geopolymer-based bifunctional supercapacitor prepared according to an embodiment of the present invention; Figure 2 Typical SEM images of the metakaolin soil polymer used in this invention; Figure 3 This is a particle size distribution diagram of the metakaolin used in this invention; Figure 4 Images of the nickel foam current collector used in this invention; Figure 5 Image of the completed activated carbon electrode; Figure 6 The curve shows the change in compressive strength over the curing period; Figure 7 A bar chart comparing the water absorption rates of samples of different moduli after 28 days of curing; Figure 8 Mercury intrusion porosimetry pore size distribution curves and relative volume fraction diagrams for polymer films with different moduli; Figure 9 Comparison of SEM morphology of polymer films with different moduli at different magnifications; Figure 10 The representative XRD pattern of sample M12; Figure 11 XRD comparison images of samples M06, M08, M10, M12 and M14; Figure 12 10 mV·s -1 Cyclic voltammetry curves at scan rate; Figure 13 0.25 A·g -1 Constant current charge-discharge curves at current density; Figure 14 The Nyquist AC impedance curve of the device under open-circuit voltage; Figure 15 This is a line graph showing the specific capacitance as a function of the modulus, calculated from the GCD curve. Figure 16 One of the physical demonstration images of the dual-function supercapacitor assembled in this invention powering a green LED light bulb; Figure 17 The second physical demonstration image shows the dual-function supercapacitor assembled according to the present invention powering a green LED light bulb. Detailed Implementation
[0018] In view of the shortcomings of the existing technology, and through long-term research and extensive practice, the technical solution of this invention has been proposed. The following will further explain and illustrate the technical solution, its implementation process, and its principles.
[0019] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.
[0020] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials used in the following embodiments are commercially available.
[0021] like Figure 1 As shown, this embodiment of the invention provides a method for preparing a geopolymer-based bifunctional supercapacitor, comprising the following steps: Prepare an alkaline activator solution, wherein the modulus of the alkaline activator solution is 0.6 to 1.4, and the alkaline equivalent based on sodium oxide is 11%; Metakaolin and the alkaline activator solution were mixed and stirred at a liquid-to-solid ratio of 0.5 to obtain geopolymer slurry; The geopolymer slurry is cast into a mold and cured to obtain a geopolymer structured electrolyte membrane. An electrolyte solution is injected into the geopolymer structured electrolyte membrane; Two activated carbon electrodes are respectively attached to opposite sides of the geopolymer electrolyte membrane to obtain a dual-function supercapacitor.
[0022] The present invention also provides a geopolymer-based bifunctional supercapacitor, comprising a geopolymer-structured electrolyte membrane, an electrolyte solution, and two symmetrically arranged activated carbon electrodes; the geopolymer-structured electrolyte membrane is formed by polymerizing metakaolinite through an alkaline activator with a modulus of 0.6 to 1.4, and the geopolymer-structured electrolyte membrane has an intrusive porosity of 40% to 44% and a most probable pore size of 119 nm to 430 nm. Figure 16 and Figure 17 A physical demonstration image showing the geopolymer-based bifunctional supercapacitor (three connected in series) assembled according to this invention powering a green LED light bulb; Figure 16 It is in the powered-on state. Figure 17 The device is not powered on.
[0023] To better understand the technical solution of the present invention, the following detailed discussion is provided in conjunction with specific embodiments.
[0024] Example 1 This embodiment provides a method for preparing a geopolymer-based bifunctional supercapacitor. 100 parts by mass of metakaolin are weighed. Sodium silicate water glass with an initial modulus of 3.30 is mixed with solid sodium hydroxide, controlling the alkali equivalent (as Na₂O) at 11% and the liquid-to-solid ratio (L / S) at 0.5, to prepare an alkaline activator solution with a modulus (SiO₂ / Na₂O molar ratio) of 0.6. The metakaolin is mixed with the above activator solution and placed in a planetary mortar mixer, stirred sequentially at low speed for 120s and high speed for 120s to obtain a geopolymer slurry. The slurry is poured into a mold, allowed to stand at room temperature for 24 hours, demolded, and then cured at room temperature for 28 days to obtain a geopolymer-structured electrolyte membrane. The membrane is immersed in a 0.5 mol / L Na₂SO₄ aqueous solution until saturated. Activated carbon, conductive carbon black, and polytetrafluoroethylene binder were mixed in a mass ratio of 85:10:5 and then pressed onto a nickel foam current collector to prepare a loading capacity of 5 mg / cm². 2Two activated carbon electrodes were attached to both sides of a separator and thermoplastic encapsulated to obtain a supercapacitor. Mercury intrusion porosimetry (MIP) testing showed that the separator obtained in this embodiment had an intrusive porosity of 43.82%, a most probable pore size of 428.5 nm, and a pore volume percentage larger than 200 nm of 39.44%. The 28-day compressive strength of this embodiment was tested to be 4.8 MPa, and the specific capacitance at a current density of 0.25 A / g was 228.5 F / g.
[0025] Example 2 The preparation method in this embodiment is basically the same as that in Example 1, except that the modulus is controlled to be 1.0 when preparing the alkaline activator solution. The other process parameters (alkali equivalent 11%, liquid-solid ratio 0.5, dual-speed stirring, curing regime, electrode ratio) remain the same.
[0026] According to MIP testing, the permeable porosity of the membrane obtained in this embodiment is 42.85%, the most probable pore size is 423.7 nm, the volume ratio of pores larger than 200 nm decreases to 35.47%, and the proportion of fine pores in the 50-200 nm range increases to 5.80%. Testing showed that the 28-day compressive strength of this embodiment increased to 8.1 MPa; at a current density of 0.25 A / g, the constant current charge-discharge curve exhibited a symmetrical triangle, and the specific capacitance reached its optimal value of 232.51 F / g. SEM observation showed that the M10 sample had sufficient gel encapsulation and filling, a more uniform pore structure, and a reduction in defective pores.
[0027] Example 3 The preparation method in this embodiment is basically the same as that in Example 1, except that the modulus is controlled to be 1.2 when preparing the alkaline activator solution. All other process parameters remain the same.
[0028] According to MIP testing, the permeable porosity of the membrane obtained in this embodiment was reduced to 40.92% (falling within the range of 40%~44%), the most probable pore size was significantly refined to 140.0 nm (near the midpoint between the lower limit of 119 nm and the upper limit of 430 nm), the volume ratio of pores larger than 200 nm dropped sharply to 2.54%, and the pore size composition changed from coarse interconnected pores to dominant medium-fine pores of 50~200 nm (accounting for 32.11%). Testing showed that the 28-day compressive strength of this embodiment was significantly improved to 11.5 MPa, the water absorption rate decreased to 33.55%, and the specific capacitance at a current density of 0.25 A / g was 191.5 F / g. This embodiment achieves an excellent balance between mechanical load-bearing capacity (11.5 MPa) and energy storage performance.
[0029] Example 4 The preparation method in this embodiment is basically the same as that in Example 1, except that the modulus is controlled to be 1.4 when preparing the alkaline activator solution. All other process parameters remain the same.
[0030] According to MIP testing, the permeable porosity of the membrane obtained in this embodiment is 40.25%, the most probable pore size is further refined to 119.0 nm, the volume ratio of pores with a diameter greater than 200 nm is only 1.51%, while the proportion of small pores of 20-50 nm and 0-20 nm is significantly increased, and the total pore area is greatly increased to 21.58 m². 2 / g. Testing showed that this embodiment exhibited the highest 28-day compressive strength, reaching 15.3 MPa; its specific capacitance at a current density of 0.25 A / g was 183.48 F / g. EIS testing revealed that while the high-modulus sample had a slightly higher equivalent series resistance due to its dense and tortuous pores, it possessed the best structural strength.
[0031] Example 5 The preparation method in this embodiment is basically the same as that in Example 1, except that the modulus is controlled to be 1.1 when preparing the alkaline activator solution. All other process parameters remain the same.
[0032] The membrane obtained in this embodiment has an intrusive porosity of 41.5%, a most probable pore size of 280.0 nm, and a pore volume ratio of approximately 18.5% for pores larger than 200 nm, effectively reducing the large pores in the low-modulus sample while retaining an appropriate amount of interconnected channels. Testing showed that the 28-day compressive strength of this embodiment was 9.8 MPa, and the specific capacitance at a current density of 0.25 A / g was 210.0 F / g. Compared to Example 3 (modulus 1.2), the electrochemical performance was improved by approximately 9.6%; compared to Example 2 (modulus 1.0), the compressive strength was improved by approximately 21%. This embodiment further verifies that a modulus of alkali activator in the range of 1.0 to 1.2 can effectively balance structural strength and ion transport rate, representing the optimal process window for this invention.
[0033] The invention will be further discussed in detail below with reference to experimental examples.
[0034] Experiment 1 1. Materials and Methods The precursor of the cementitious material used in this experiment was metakaolin (MK), which was purchased from Gongyi Chenyi Refractory Abrasive Co., Ltd., with an activity index greater than 110. The specific chemical composition is shown in Table 1. Figure 2 Typical SEM images of metakaolin soil polymers used in this application; Figure 3 Particle size distribution of metakaolin. The electrode active material used is Kuraray capacitor carbon YP-50F. According to the supplier's technical data, this activated carbon has a high BET specific surface area (approximately 1692 m²). 2The particle size distribution (by laser diffraction) is approximately 0.30 g / mL, with a bulk density of approximately 0.30 g / mL and an ash content of approximately 0.2%. The particle size distribution is approximately 1.9 μm for D10, 5.6 μm for D50, and 9.7 μm for D90. The conductive agent used is SuperPLi conductive carbon black (TIMCAL), which has a BET specific surface area of approximately 62 m². 2 / g, ash content ≤0.05%. The binder is polytetrafluoroethylene (PTFE, KELOD). Nickel foam (Jiangsu Zhenyuhong New Material Co., Ltd.) is used as the current collector; it has a continuous porous structure, a thickness of 1.5±0.1mm, and an areal density of 667±20g / m³. 2 Aluminum electrode tabs were purchased from Ouli Electrochemical Materials Co., Ltd. Anhydrous sodium sulfate (Na₂SO₄, AR), sodium hydroxide (NaOH), anhydrous ethanol, and liquid sodium silicate (water glass) were all purchased from Sinopharm Chemical Reagent Co., Ltd. All water used in this study was deionized water, and all chemical reagents were ready for direct use without further purification.
[0035] Table 1 Chemical composition of metakaolin 2. Preparation of activators, geopolymers and bifunctional electrolytes This study used a composite alkali of NaOH and Na₂SiO₃ as the activator, fixing the alkali equivalent (based on Na₂O) at 11%. Activator solutions with different moduli were prepared by adjusting the SiO₂ / Na₂O molar ratio (i.e., modulus). The initial modulus of the water glass used was 3.30 (SiO₂: 26.98 wt%, Na₂O: 8.53 wt%, density 1.366 g / mL). -1 Based on the definition of modulus and the conservation relationship of Na2O, calculation formulas for the mass of water glass and sodium hydroxide are established (see formulas (1)–(4)) to determine the required amount of Na2SiO3 and NaOH for each target modulus.
[0036] Assuming the modulus of the activator is 'a', based on the explanation of modulus above, we can conclude that: (1) Let xg be the mass of water glass (g) and yg be the mass of sodium hydroxide. The relationship between x and y can be summarized as follows: (2) (3) Based on the above three formulas, the relationship between the mass of water glass and the mass of sodium hydroxide can be calculated.
[0037] The AE (alkali equivalent) percentage is 11%, which is the percentage of Na₂O in the cementitious material raw materials. Based on Na… + From conservation, we can conclude that: (4) This study designed moduli a = 0.6, 0.8, 1.0, 1.2, and 1.4, with a uniform liquid-to-solid ratio (L / S) of 0.5. "Liquid" includes water in the water glass solution and additional deionized water, while "solid" includes metakaolin, solid NaOH, and the solid portion of the water glass. In preparation, NaOH was first prepared into a solution and naturally cooled to room temperature. Then, it was mixed with a measured amount of water glass to prepare the activator solution for the target modulus. Subsequently, metakaolin and the activator were mixed according to the designed ratio and stirred in a planetary mortar mixer according to the standard cement program (low speed 120s + high speed 120s) until the slurry was homogeneous, resulting in a metakaolin-polymer slurry. The samples were named M06, M08, M10, M12, and M14 based on their moduli.
[0038] The uniformly mixed slurry was poured into 20mm×20mm×20mm cubic molds (for compressive strength testing) and 20mm×20mm×2mm molds (for electrochemical testing), respectively. After standing at room temperature for 24 hours, the slurry was demolded and cured at room temperature for 28 days. Subsequently, 0.5 mol·L⁻¹ of slurry was injected into the geopolymer membrane. -1 Na2SO4 electrolyte solution is used to saturate and wet the membrane, which is then used as a structural electrolyte membrane.
[0039] 3. Assembly of supercapacitors 85 wt% activated carbon and 10 wt% conductive carbon black were dry-mixed evenly in an agate mortar to ensure micro-dispersion. PTFE emulsion (5 wt%) and an appropriate amount of anhydrous ethanol were added dropwise and ground thoroughly until agglomerates with a certain plasticity were formed. The agglomerates were then uniformly pressed onto a pretreated nickel foam substrate using a roller press and dried at 80°C for 1 hour to remove residual solvent. An AC electrode with a loading of 5 mg cm⁻² was obtained. Figure 4 Images of nickel foam current collectors used in this application; Figure 5 Image of the prepared activated carbon electrode. The structural supercapacitor adopts a symmetrical two-electrode structure, consisting of two AC electrodes sandwiching a geopolymer membrane saturated with Na2SO4 solution, forming a sandwich-type module. The naming of the resulting SSC is consistent with the corresponding geopolymer membrane. The module is encapsulated with a thermoplastic film, leaving only the tabs exposed to reduce environmental interference.
[0040] 4 Characterization methods XRD analysis was performed using a Bruker D2 Phaser diffractometer (Germany) with CuKα radiation (λ = 0.154 nm), a tube voltage of 40 kV, a current of 40 mA, and a 2θ scan range of 5–80°. The MK particle size distribution was measured using a laser particle size analyzer (Malvern Mastersizer 2000). Microstructure was observed using a scanning electron microscope (SEM, ZEISS Sigma 300). Pore structure parameters were characterized using a mercury porosimeter (Micromeritics AutoPoreV) to obtain porosity, pore size distribution, and volume fractions for different pore size ranges. Compressive strength was determined using a JES-300 concrete compressive strength testing machine with a loading rate of 2.4 kN / s. -1 Calculate the compressive strength according to formula (5): (5) Where fc is the compressive strength (MPa), F is the failure load pressure (KN), and A is the area under pressure (m2).
[0041] In the water absorption test, the 28-day-old specimen was first dried at 100℃ for 48 hours, and its mass was measured as m0. The dried specimen was then placed in a water tank, supported by two steel bars to ensure complete immersion. After immersion for 48 hours, it was removed, the surface water was wiped off with a dry, damp cloth, and its mass was measured as m1. The water absorption rate formula is: (6) All electrochemical experiments were conducted at room temperature using a CHI660E workstation. A symmetrical two-electrode system was used to test the SSC, with two capacitive carbon electrodes serving as the positive and negative electrodes, respectively. Electrochemical impedance spectroscopy (EIS) was performed in the frequency range of 0.01 Hz–1 MHz, with a perturbation voltage of 5 mV and an initial voltage set to the open-circuit voltage. Cyclic voltammetry (CV) was performed within a voltage window of 0–1 V at a scan rate of 10 mV s⁻¹. Galvanostatic charge-discharge (GCD) was performed within a voltage window of 0–1 V, with a current density of 0.25 A g⁻¹, where the mass m was the total mass of the active materials on both electrodes. Based on the GCD curves, the specific capacitance Cm (F g⁻¹) of the SSC was calculated using equations.
[0042] Chemical tests were performed on a CHI660E electrochemical workstation using a symmetrical two-electrode system (two AC electrodes serving as the positive and negative electrodes, respectively). The CV scan voltage window was 0–1 V, and the scan rate was 10 mV / s. -1 The GCD test was performed within a 0–1V window at a current density of 0.25Ag. -1 Where mass m is the total mass of the active materials of the two electrodes. The specific capacitance Cm of the SSC is calculated according to formula (7): (7) Where j is the current density (Ag) -1 Δt is the discharge time (s), and ΔV is the effective discharge voltage (V) after deducting the IR drop. The EIS test is performed near the open-circuit voltage, with a frequency range of 0.01Hz–1MHz and an AC disturbance voltage amplitude of 5mV.
[0043] Results and Discussion: Performance and Structural Evolution of Geopolymer Structured Electrolytes (Membranes) Table 1 shows the XRF results of MK. SiO2 and Al2O3 are the main components, with a SiO2 / Al2O3 mass ratio of 1.31, indicating that the precursor possesses typical aluminosilicate framework characteristics and can undergo depolymerization-condensation under alkaline excitation conditions to form a three-dimensional gel network. MK particles exhibit an irregular plate-like morphology, and the particle size distribution shows an average particle size of 6.52 μm, which is beneficial for sufficient contact with alkaline solution and promotes the reaction.
[0044] The core objective of developing a dual-function supercapacitor combining structure and energy storage is to achieve energy storage while bearing mechanical loads. Therefore, it is necessary to evaluate the mechanical and water absorption behavior of polymer membranes with different moduli. Figure 4 The graphs show the mechanical and water absorption properties of polymer films with different moduli. 4a is the curve of compressive strength changing with curing age; 4b is a bar chart comparing the water absorption rate of samples with different moduli after 28 days of curing. Figure 6 The results showed that the compressive strength of all samples gradually increased with the extension of the curing period, indicating that metakaolinite continuously underwent a dissolution-condensation reaction under alkaline activation conditions, resulting in a continuously improved gel network and promoting matrix densification. At 28 days, the compressive strength increased significantly with increasing modulus, with sample M14 reaching the highest strength of 15.3 MPa, followed by sample with a modulus of 1.2, indicating that a higher modulus is beneficial for constructing a more continuous and load-bearing geopolymer skeleton. Meanwhile, Figure 7 The results show that the water absorption rate decreases in stages over 28 days: the water absorption rate remains at 36.53–36.71% in the low modulus range (0.6–1.0), while it significantly decreases to 33.55% and 33.21% when the modulus is increased to 1.2 and 1.4, respectively. This result indicates that increasing the modulus effectively reduces rapid water wetting and capillary absorption, reflecting changes in the material's pore structure and connectivity that favor densification. To further clarify the influence of modulus changes on pore size distribution, MIP (Medium Infiltration Permeability) tests were conducted. The results are shown in Table 2 and... Figure 8 As shown.
[0045] Table 2. MIP pore structure parameters of geopolymer membranes with different moduli Combined with Table 2, Figure 8The pore size distribution curves and pore size classification volume fraction results can further reveal the intrinsic laws of pore structure evolution under modulus regulation and provide direct structural evidence for the differences in water absorption and mechanical properties. Overall, with increasing modulus of the alkaline activator, the intrusive porosity of the geopolymer membrane (obtained by MIP testing) shows a decreasing trend, decreasing from 43.82%, 43.28%, and 42.85% for moduli of 0.6, 0.8, and 1.0, respectively, to 40.92% and 40.25% for moduli of 1.2 and 1.4. The peak positions of the pore size distribution also show significant refinement: the most probable pore size of the low-modulus samples (0.6–1.0) remains relatively stable at 427–428.5 nm, while when the modulus increases to 1.2 and 1.4, the most probable pore size significantly decreases to 149 nm and 119 nm, respectively. This indicates a shift in the pore structure from being dominated by large pores to being dominated by small pores, which can be attributed to the effective suppression of macroscopic defect pore retention by gel condensation and framework densification. The refinement of pore size and the reduction in porosity are consistent with the change in water absorption rate over 28 days.
[0046] From the perspective of pore size gradation contribution, low-modulus samples (0.6–1.0) are still dominated by pores >200nm, with this pore segment accounting for as high as 39.44% and 39.24% in moduli 0.6 and 0.8, respectively, while it drops to 35.47% in moduli 1.0, indicating that the proportion of harmful macropores in the 1.0 sample has been somewhat suppressed. At the same time, the proportion of pores in the 50–200nm range increases to 5.80%, higher than the 3.34% and 3.25% in moduli 0.6 and 0.8, making the pore structure more uniform. This can explain why the 1.0 modulus achieves higher compressive strength despite similar differences in total porosity and water absorption compared to 0.6 and 0.8. Its advantage is more likely due to the synergistic effect of "macropore reduction + pore size gradation optimization" rather than the single factor of porosity.
[0047] With the modulus increased to 1.2 and 1.4, the pore size composition underwent significant adjustments. The contribution of the >200nm pore segment plummeted to 2.54% and 1.51%, respectively, and the pore structure shifted from being dominated by large pores to being dominated by the 50–200nm pore segment (32.11% and 30.69%), accompanied by an increase in the proportion of fine pores in the 20–50nm (4.15% and 5.67%) and 0–20nm (2.12% and 2.37%) ranges. Correspondingly, the total pore area increased from 5.46–6.47 μm in the low modulus range. 2 / g increased significantly to 17.44 and 21.58m 2 / g reflects a significant increase in the number of pores and the inner surface area. The combined characteristics of "decreased porosity - refined pore size - redistribution of pore size" weaken the interconnected coarse capillary network, reduce the rapid wetting of water and capillary water absorption capacity, thereby supporting a further reduction in the water absorption rate of high-modulus samples and laying the pore structure foundation for their superior mechanical performance.
[0048] Further integration Figure 9Multi-scale SEM morphology of samples with different moduli can provide intuitive verification of differences in compressive strength, water absorption, and pore structure revealed by MIP. At the 100 μm scale, the surface of the M06 matrix is rougher and more porous, with locally visible heterogeneous porous areas and pore traces. Magnified to 20 μm and 5 μm, the particle packing and gel phase distribution are still relatively discrete, with some areas of insufficient bonding and exposure of incompletely reacted MK particles, suggesting that it is more likely to retain large, interconnected defect pores. This morphological feature is consistent with the macropore dominance and large pore size peaks of low-modulus samples in MIP, and also matches their higher water absorption and weaker load-bearing framework.
[0049] Compared to M06, M10 exhibits improved matrix continuity and uniformity across all three scales, with more thorough gel encapsulation and filling of particles, and a relative reduction in macroscopic loose regions and coarse defect pores. Although its total porosity and water absorption are similar to those of the low-modulus sample, the homogenization of pore structure and the suppression of macropores observed in SEM suggest that the mechanical advantages are more likely due to the synergistic effect of optimized pore size distribution and defect pore reduction, rather than a single factor of porosity.
[0050] Further increasing the modulus to M12 and M14, SEM revealed a more compact matrix, a more continuous gel network, a significant reduction in macroscopic defects (pores), and a refined overall pore morphology. This trend aligns with the MIP results of "decreased porosity - migration of peak pore size to smaller pores - transformation of pore size composition from macropores to mesopores." Therefore, the interconnected coarse capillary network in high-modulus samples is effectively weakened, providing visual evidence of reduced water absorption and increased compressive strength at the microscopic morphology level, which corroborates the aforementioned pore structure analysis.
[0051] Refer to the XRD patterns of geopolymer films with different moduli, among which Figure 10 7b shows the representative XRD pattern of sample M12; 7b shows a comparison of the XRD patterns of samples M06, M08, M10, M12, and M14. Figure 10 As can be seen, all samples exhibited broad, diffuse humps within the range of 2θ≈18–35°, which is a typical diffraction characteristic of amorphous (NASH) gels in alkali-activated metakaolin systems, indicating that the geopolymer reaction products are predominantly amorphous gel phase. Several sharp diffraction peaks superimposed on the humps are mainly located at 2θ≈20.8°, 26.6°, 36.5°, 50.1°, and 59.9°, corresponding well to the characteristic diffraction peaks of quartz (SiO2) in the PDF card, indicating that some unreacted quartz crystals were retained in the samples, consistent with the mineral composition of the metakaolin raw material. Besides quartz, no new significant crystalline hydration products were detected, further demonstrating that the geopolymerization process under different modulus conditions mainly forms an amorphous aluminosilicate network, rather than a large amount of crystalline phase.
[0052] contrast Figure 11 The combined spectra of M06–M14 show that the positions of the quartz diffraction peaks in samples with different moduli are basically consistent, with only slight differences in intensity. This indicates that quartz mainly acts as an inert aggregate in the system, and its crystal structure and content do not change much with modulus. In contrast, the morphology of the amorphous hump in the 18–35° range changes slightly with modulus: the hump of medium-modulus samples (such as M10 and M12) is relatively fuller, and the background is raised, reflecting an increase in the amount and degree of polymerization of aluminosilicate gel; while at higher moduli, the hump morphology changes more slowly, and no further crystalline phases appear. This phenomenon is consistent with the trend of "reduced porosity, refined pore size, and denser matrix" revealed by MIP and SEM, indicating that the differences in macroscopic mechanical and electrochemical properties caused by different moduli are not due to changes in mineral types, but mainly to adjustments in the amount and spatial structure of amorphous NASH gel.
[0053] Electrochemical performance of structural supercapacitors: Figure 12 SSCs assembled for polymer films with different basic activator moduli at 10 mV / s -1 The CV curves for each sample showed a relatively ideal rectangular shape without obvious redox peaks, indicating that the device primarily exhibits electrochemical double-layer capacitance behavior. In terms of envelope area, the CV response decreased overall with increasing modulus, indicating a gradual decrease in the contribution of the indicative capacitance. This trend is consistent with the pore structure evolution shown in the MIP. As the modulus increases, the intrusive porosity of the geopolymer membrane decreases, and the pore structure shifts from being dominated by large pores to being dominated by small pores. In low-modulus samples, the proportion of pores >200 nm is higher and their connectivity is stronger, which is beneficial for rapid electrolyte wetting and ion migration within the membrane, thus exhibiting a larger effective capacitance response at this scan rate. Conversely, in high-modulus samples, the pore size is significantly refined, accompanied by a decrease in total porosity. The macroscopic interconnected pore network is suppressed, reducing ion accessibility and rapid response capability, thereby leading to a decrease in the CV area.
[0054] Figure 13 The GCD curves are shown under the same current density conditions. The approximately symmetrical triangle shape of the curves indicates the reversible electrochemical characteristics of the device. A small voltage drop can be observed at the apex of the curve, indicating that the internal resistance of the supercapacitor is relatively low. This helps to prevent unnecessary energy waste during charging and discharging. The trend of specific capacitance as a function of modulus, calculated from the GCD curves, is shown in [reference needed]. Figure 15Under the same test conditions, the longer the charge / discharge time, the higher the specific capacitance. It can be clearly seen that the specific capacitance decreases with increasing modulus; the device with a modulus of 1.0 has the highest discharge specific capacitance at 232.51 Fg⁻¹, while the device with a modulus of 1.4 has the lowest at 183.48 Fg⁻¹. This indicates that the effective pores and fast transport pathways for energy storage are reduced in high-modulus samples, leading to a decrease in specific capacitance. Therefore, the porosity level and pore size composition of the geopolymer membrane jointly determine the ion storage efficiency and kinetic response of the device at a given rate. This is consistent with the analysis results of the CV curves.
[0055] Figure 14 The Nyquist curve for SSC is shown. The equivalent series resistance Res can be obtained through the intersection of the high-frequency region and the real axis. Res increases with increasing modulus, indicating that the densification of the pore structure and the significant reduction in >200nm coarse capillaries weaken the electrolyte interconnection channels and increase the resistance to ion migration. Combined with the pore size classification results, although the high-modulus sample exhibits a higher total pore area, the network dominated by fine pores may lead to higher tortuosity and a longer effective diffusion path, thus manifesting as higher internal resistance and shorter discharge time at the device level.
[0056] In summary, CV, GCD, and EIS consistently demonstrate, from both capacitive response and charge transport impedance perspectives, that as the modulus of the alkaline activator increases, the pore structure of the geopolymer membrane tends to become finer and the intrusive porosity decreases. While this structural densification is beneficial for improving the membrane's mechanical load-bearing capacity, it simultaneously weakens the rapid wetting of the electrolyte and the high-rate migration / accessibility of ions within the membrane, ultimately leading to a gradual decline in the electrochemical energy storage performance of SSC. This conclusion corroborates the pore structure evolution patterns revealed by water absorption rate and MIP.
[0057] Finally, a lighting demonstration was conducted to further validate the practical application potential of the SSC. Three SSCs were connected in series and charged to 3V, which was then used to power a small green LED bulb. The lighting lasted for more than 3 minutes, and the brightness changed over time as follows: Figure 8 As shown in the figure, this experiment demonstrates the feasibility of geopolymer-based SSC in practical energy storage applications.
[0058] This invention systematically reveals the regulatory mechanism of the modulus of an alkaline activator on the multi-scale pore structure and structural properties of metakaolinite geopolymer membranes. With increasing modulus, the geopolymer gradually evolves from a high-porosity network dominated by large interconnected pores to a more dense and continuous N-A-S-H gel skeleton dominated by fine pores. This is manifested in a decrease in intrusive porosity and water absorption, a refinement of the most probable pore size from approximately 430 nm to approximately 120–150 nm, a significant reduction in macroscopic loose regions and large defect pores in SEM, and the detection of only amorphous gel and a small amount of residual quartz by XRD. This combined effect of "porosity reduction + pore size refinement + large pore reduction" results in a steady increase in the compressive strength of the geopolymer membrane with increasing modulus, indicating that pore size gradation optimization and defect suppression are more dominant in its load-bearing capacity than porosity alone.
[0059] From an electrochemical perspective, the SSCs assembled by geopolymer separators all exhibit near-ideal double-layer capacitance characteristics, but their capacitance response and charge transport behavior are extremely sensitive to pore structure. Low-modulus samples, due to their higher macropore ratio and better interconnected channels, demonstrate greater specific capacitance and longer discharge time in CV and GCD tests. High-modulus samples, while having a denser structure, suffer from decreased electrolyte wettability and ion migration rate due to channel contraction and diffusion path tortuosity, resulting in a corresponding deterioration in specific capacitance and equivalent series resistance. The combined mechanical and electrochemical results indicate that there exists a trade-off window between structure and energy storage performance in the modulus of the alkali activator; a modulus of approximately 1.0–1.2 can maintain superior electrochemical energy storage performance while ensuring high compressive strength, providing a quantitative basis for the design of subsequent multifunctional structure-energy storage geopolymer materials.
[0060] The above descriptions are merely some embodiments of the present invention. It should be noted that those skilled in the art can make other modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the protection scope of the present invention.
Claims
1. A method for preparing a geopolymer-based bifunctional supercapacitor, characterized in that, Includes the following steps: S1. Prepare an alkaline activator solution, wherein the modulus of the alkaline activator solution is 0.6 to 1.4, and the alkaline equivalent based on sodium oxide is 11%; S2. Mix metakaolin and the alkaline activator solution at a liquid-to-solid ratio of 0.5 to obtain geopolymer slurry; The geopolymer slurry is cast into a mold and cured to obtain a geopolymer structured electrolyte membrane. S3. Inject an electrolyte solution into the geopolymer structure electrolyte membrane; S4. Two activated carbon electrodes are respectively attached to the opposite sides of the geopolymer structure electrolyte membrane to obtain a dual-function supercapacitor.
2. The method according to claim 1, characterized in that, The mixing process involves sequentially mixing at a low speed of 120 seconds and a high speed of 120 seconds in a planetary mortar mixer.
3. The method according to claim 1, characterized in that, The curing process involves: demolding after standing at room temperature for 24 hours, and then curing at room temperature for 28 days.
4. The method according to claim 1, characterized in that, The electrolyte solution is a 0.5 mol / L sodium sulfate aqueous solution.
5. A geopolymer-based bifunctional supercapacitor prepared by the method according to any one of claims 1-4, characterized in that, It includes a geopolymer structured electrolyte membrane, an electrolyte solution, and two symmetrically arranged activated carbon electrodes; The geopolymer structured electrolyte membrane is formed by polymerizing metakaolin clay with an alkaline activator having a modulus of 0.6 to 1.
4. The geopolymer structured electrolyte membrane has an intrusive porosity of 40% to 44% and a most probable pore size of 119 nm to 430 nm.
6. The dual-functional supercapacitor according to claim 5, characterized in that, The alkaline activator is a composite alkaline activator of sodium hydroxide and sodium silicate.
7. The dual-functional supercapacitor according to claim 5, characterized in that, The activated carbon electrode comprises activated carbon, conductive carbon black, and polytetrafluoroethylene binder, wherein the mass ratio of activated carbon, conductive carbon black, and polytetrafluoroethylene binder is 85:10:
5.
8. The dual-functional supercapacitor according to claim 7, characterized in that, The active material loading of the activated carbon electrode is 5 mg / cm³. 2 The activated carbon is Kuraray capacitor carbon YP-50F, and the conductive carbon black is Super P Li.
9. The dual-functional supercapacitor according to claim 5, characterized in that, In the geopolymer structured electrolyte membrane, the volume percentage of pores with a diameter greater than 200 nm is 1.5% to 39.4%.
10. The dual-functional supercapacitor according to claim 5, characterized in that, The 28-day compressive strength of the geopolymer structure electrolyte membrane is 11.5 MPa to 15.3 MPa.